Renewable Power Sources - Bonifácio, Paulo (2005)
Of all of the sources of renewable energies available one can argue that the most abundant and accessible are solar power, radiation, and the energy of the tides (70 % of the earth surface is covered by water). The tidal wave energy hasn’t seen a widespread distribution yet, mainly due to the lack of interest of the governments, most of the coastal areas of the world are exclusive responsibility of the governments, thus not easily open for private venture. Considering solar power, there exist two main fields of application, land based systems and space based systems. The former systems are still in a very embryonic phase, with Japan being the lead researcher in the field, with an experimental satellite-power station to be launched before 2010. Land based systems, on the other hand, are well studied, with major research and application programs in all known forms of solar power production. Given a minimum value of incident radiation, and applying the appropriate system, (i.e. power plant type), for any given area the solar power becomes an income-producing industry.